How management of grief associated with ending the life of an animal is taught to Australasian veterinary students. Issue 8 (27th May 2020) - Littlewood, KE; Beausoleil, NJ; Stafford, KJ; Stephens, C; Collins, T; Fawcett, A; Hazel, S; Lloyd, JKF; Mallia, C; Richards, L; Wedler, NK; Zito, S
Abstract : Objective: Veterinarians have an important role in supporting and understanding their clients' grief. Veterinary schools have a duty to teach students how best to manage grief – both that of the students/future veterinarians and the clients. This study explores how grief management, associated with ending the life of an animal, was taught to students in eight Australasian veterinary schools. Methods: A questionnaire‐style interview guide was used by a representative at each university to conduct structured interviews with educators in a snowball sampling approach. Educators were interviewed about the teaching of grief management for four categories of animals: livestock, equine, companion and avian/wildlife. The terms used by participants to describe what they taught were grouped into common themes. Teaching was defined by individual participants and included structured and unstructured approaches. The stage in the degree (preclinical or clinical years) that grief management was taught in the veterinary curriculum and by whom (e.g. clinicians or psychologists) is also described. Results: Grief management was taught more in preclinical than clinical years. However, due to how grief was characterised, much of this teaching was general 'nonspecific' teaching that included all categories of animals. Client grief was taught more generically, whereas, grief of veterinarians was taught using specific examples given by clinicians. Conclusion: A more robust end‐of‐life (EoL) management curriculum that includes all aspects of grief management is likely to increase job satisfaction, client happiness and professional satisfaction.